Evolutionary adaptations to new environments generally reverse plastic phenotypic changes - Wei-Chin Ho (Nature Communications, 2018)
Phenotypic plasticity has been suggested to facilitate survival in new environments and subsequent adaptation. Here, the authors reanalyze transcriptomic data from experimental evolution studies in combination with computational metabolic network analysis and show that genetic adaptation tends to reverse plastic changes in order to recover fitness.